Building trust : a manager's guide to business success - Shurtleff, Mary Galbreath (Crisp Pub. Menlo ParkUS, 1998)
Explains the concept of trust and shows how instinct, past and current experiences influence one's choice to exercise trust. Identifies 4 consequences of lack of trust in organizations; and presents strategies for encouraging trust at both at the managed and the manager levels.